667. Real-world Experience of Cefiderocol with Pseudomonas aeruginosa in the PROVE (Retrospective Cefiderocol Chart Review) Study. (15th December 2022) - Marcella, Stephen; Carr, Amy L; Kobic, Emir; Nguyen, Sean; Zhou, Anan
Abstract: Background: Gram-negative (GN) bacterial resistance is an urgent global health problem. Cefiderocol (CFDC) is active against many resistant GN pathogens, including Pseudomonas aeruginosa (PA). PROVE is an ongoing international, retrospective study assessment of CFDC use for Gram-negative infections (GNI). Methods: Patients were eligible if they received ≥ 72 hours of CFDC. Patient and pathogen characteristics, hospital course, and antibiotic treatment patterns were described. All-cause mortality (ACM) at 14 and 30 days and clinical cure were examined as outcomes, overall, and by key characteristics such as pathogen susceptibility (determined at the local level), patient demographics, infection site, and severity of illness. Serious adverse drug reactions (SADR) were recorded. Results: To date, 123 patients treated with CFDC at 12 sites were included. Sixty-five patients had PA as a pathogen, either alone (N=45) or in combination with another pathogen (N=20) attributed to starting CFDC. The median age was 54 years; 68% were male. The most prevalent comorbidity was diabetes with end stage organ damage (N=15, 23%). CFDC was given in an ICU setting in 54 (82%) patients. Vasopressors and mechanical ventilation were required in 42% and 62%, respectively. Most (91%) PA were carbapenem resistant. The median time from a positive culture to start of CFDC was 6 days. CFDC monotherapy was used in 75%. The most common GN antibiotic class used concurrently with CFDC was aminoglycosides (N=7). Targeted therapy with CFDC against pathogens of known susceptibility with or without prior GN antibiotics accounted for 80% of use. The remainder was used for salvage (15%) or empirically (2%). Susceptibility testing to CFDC, available for 54 cultures (54 patients), showed 94% (51/54) were susceptible. Post-CFDC initiation 14- and 30-day all-cause mortality (ACM) was 9% (95% CI: 3%-19%) and 23% (95% CI: 14%-35%) respectively. Clinical resolution was achieved in 66% (95% CI: 53% -77%). Thirty-day ACM for susceptible pathogens was 25% (13/51). Cefiderocol Use Patterns in Pseudomonas aeruginosa Conclusion: Real-world use of CFDC for PA demonstrated that most patients had multiple comorbidities and were severely ill. These data suggest that CFDC is being used appropriately with little empirical use in patients with few treatment options. Disclosures: Stephen Marcella, MD, MPH, Shionogi: Shionogi employee|Shionogi, Inc: Employee Amy L. Carr, PharmD, BCIDP, Shionogi: Advisory Board Sean Nguyen, n/a, Shionogi: Employee Anan Zhou, MPH, Shionogi, Inc: contracting work for Shionogi, Inc.